Litsom k litsu . Litsom k litsu . Face to Face . Лицом к лицу - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interviews with the painter Vladlen Gavrilchik and the art dealer Anna Zotikova. Featured in the program: Gavril'chik, Vladlen Vasil'evich (Painter) Contributors: Zhukovskaia, Ol'ga (Anchor) Интервью с художником Владленом Гаврильчиком и арт-дилером Анной Зотиковой. В программе участвуют: Гаврильчик, Владлен Васильевич (Художник) Создатели: Жуковская, Ольга (Ведущий/Ведущая)